1993
DOI: 10.1095/biolreprod48.5.947
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Neonatal Diethylstilbestrol Exposure on Volume of the Sexually Dimorphic Nucleus of the Preoptic Area of the Hypothalamus and Pituitary Responsiveness to Gonadotropin-Releasing Hormone in Female Rats of Known Anogenital Distance at Birth1

Abstract: The effects of neonatal diethylstilbestrol (DES) exposure on the volume of the sexually dimorphic nucleus of the preoptic area of the hypothalamus (SDN-POA) and on GnRH-stimulated LH secretion were investigated in castrated female rats of known anogenital distance (AGD) at birth. The AGD was measured in females on the day of birth, and 0.1 microgram DES or corn oil was injected from Days 1 through 10 of life. The volume of the SDN-POA was significantly larger in animals that had received DES than in those that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Although the underlying mechanism (or mechanisms) for such a finding is as yet unknown, AGD has been positively associated with the number of recruited ovarian follicles in women ( Mendiola et al 2012 ). In rat litters, female siblings with longer AGDs had greater pituitary responsiveness to gonadotropin releasing hormone than their sisters with shorter AGDs ( Faber et al 1993 ). The results from those studies suggest that changes associated with altered AGD in females brought about by in utero exposure to may result in reduced fertility in the female offspring.…”
Section: Discussionmentioning
confidence: 95%
“…Although the underlying mechanism (or mechanisms) for such a finding is as yet unknown, AGD has been positively associated with the number of recruited ovarian follicles in women ( Mendiola et al 2012 ). In rat litters, female siblings with longer AGDs had greater pituitary responsiveness to gonadotropin releasing hormone than their sisters with shorter AGDs ( Faber et al 1993 ). The results from those studies suggest that changes associated with altered AGD in females brought about by in utero exposure to may result in reduced fertility in the female offspring.…”
Section: Discussionmentioning
confidence: 95%
“…In utero and postnatal exposures increased the size of SDN-POA in females thereby defeminizing the region [245]. It was also found that PND1-10 treatment led to a significant reduction in the levels of LH secreted although a similar effect was not found when the exposure was prenatal (E16-20), highlighting the importance of DES actions on the neuroendocrine circuits [246]. …”
Section: Edcs and Their Effects On The Female Reproductive Systemmentioning
confidence: 99%
“…The development of many neural sex differences, including those of the MPN, depends on the aromatization of testosterone to oestradiol within the brain. Perinatal treatment of females with the synthetic oestrogen, diethylstilbestrol, masculinizes brain and behaviour (8–10), while similar treatment of males with aromatase inhibitors demasculinizes brain and behaviour (11–14).…”
mentioning
confidence: 99%